Language and Gender in Bubunan, Buleleng Regency - Made Sri Ayu Magreani (Linguistics Initiative, 2022)
This research discusses language and gender in the sociolinguistic field with the purposes of finding out what are the vocabularies that is commonly used by the female teenagers and the male teenagers in Bubunan Village. Thus, this research is included as the types of observational research. In collecting the data of this research, the researcher conducted observation through the teenagers’ conversation in Bubunan Village and sometimes the researcher will involve in the conversation. The result of this research is the female teenagers more commonly using the standard vocabularies in their communication. When the female teenagers delivering a bad truth, they will choose polite words, so they are not using rude words and not hurting the speakers feeling. Meanwhile, the male teenagers commonly using the rude words to show their closeness and just being straightforward. In the interaction between male and female when they have interested each other, they will choose the polite words and speak softly. In the other hand, in the interaction between male and female teenagers if they have not interested each other or their relationship is close enough as a friend, they will speak bluntly.